A calculating method for the electromagnetic shielding effectiveness of metal fiber blended fabric. Issue 9 (May 2018) - Liang, Ranran; Cheng, Wenjuan; Xiao, Hong; Shi, Meiwu; Tang, Zhanghong; Wang, Ni
In order to obtain a simple and accurate calculation method of shielding effectiveness for woven fabric containing metal fiber yarns, a conductive grid structure model composed of two parallel metal yarn periodic arrays was established. The two periodic arrays were cross-arrangement. The calculation formula of shielding effectiveness for the fabric was deduced through the transfer matrix of the electromagnetic field. The theoretical value of shielding effectiveness of the fabric using the theoretical formula and the measured value tested by the shielding chamber method were compared. Both sets of data were analyzed respectively from the metallic yarn periodic spacing, diameter, electric conductivity, electromagnetic wave polarization direction, and the weaving angle. The result shows that a reasonable agreement between the theoretical value and the measured value has been achieved in a frequency range from 4 to 14 GHz. This shows that the theoretical calculation model is simple, highly precise, and is valuable for the design and development of fabric containing metal fiber yarns. It can be used for estimating the electromagnetic shielding effectiveness of the fabric.